Dušan Karpatský a česko-chorvatské literární vztahy - Ivačić, Matija (Przekłady Literatur Słowiańskich, 2023)
This paper deals with the contribution of Dušan Karpatský (1935—2017) to the reception of Croatian literature in the Czech Republic, and Czech literature in Croatia since the 1960s until the present day. In his numerous translations, Karpatský worked tirelessly to introduce Czech readers to the achievements of Croatian (and Yugoslav) literature, and vice versa. By selecting texts for his translations that were as current as possible, and by meeting high aesthetic criteria, made him influential in both cultural milieus where he played the role of an intermediary. His work in lexicography, bibliography, history of literature and non-fiction is also of great importance. His research has made Croatian culture permanently indebted to him because he discovered and translated into Croatian the Prague Papers, written in Czech by the Croatian politician Stjepan Radić, and because he discovered a seven-language dictionary written by the Prague Benedictine monk Peter Loderecker, which was based on a five-language dictionary written by Faust Vrančić. Owing to all of the above, and much more, Karpatský is considered a key figure in literary and cultural communication between Croatia and the Czech Republic in the last six decades.